La educación y el Feminismo en el pensamiento de Gabriela Mistral - Prada Ortíz, Grace (2007)
Historically, women have been excluded from participating in society’s constitution, as well as all knowledge construction processes; nonetheless, they have confronted with struggles with the purpose of transforming their condition. Gabriela Mistral projected her thinking towards a change of ideology in the Latin American society. Her ideas, actions in defense of women from socially vulnerable classes have encouraged more equity in education and labour issues.